2006
DOI: 10.1093/ajcn/84.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Weight, shape, and mortality risk in older persons: elevated waist-hip ratio, not high body mass index, is associated with a greater risk of death

Abstract: Current guidelines for BMI-based risk categories overestimate risks due to excess weight in persons aged >/=75 y. Increased mortality risk is more clearly indicated for relative abdominal obesity as measured by high WHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
232
2
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(260 citation statements)
references
References 48 publications
12
232
2
14
Order By: Relevance
“…The ideal BMI may be higher in older adults than in middle-aged adults. It was recently reported in approximately 4000 persons aged 75 years and older that WHR rather than WC predicted mortality in nonsmoking men and women, mainly because of the association with cardiovascular deaths (54). In the Health Professionals Study, in men 65 years and older, WC and WHR were significantly related to CVD mortality (51).…”
Section: Clinical Targeting Of Higher Risk Obesitymentioning
confidence: 99%
“…The ideal BMI may be higher in older adults than in middle-aged adults. It was recently reported in approximately 4000 persons aged 75 years and older that WHR rather than WC predicted mortality in nonsmoking men and women, mainly because of the association with cardiovascular deaths (54). In the Health Professionals Study, in men 65 years and older, WC and WHR were significantly related to CVD mortality (51).…”
Section: Clinical Targeting Of Higher Risk Obesitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Weight loss is known to be associated with improvement of intermediate risk factors for disease, 8 suggesting that weight loss would also reduce mortality. Although four retrospective, bariatric cohort studies have indicated that this may be the case, 9-12 the prospective, controlled, interventional studies showing that weight loss is in fact reducing mortality have been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was lowest in the BMI's between 24.6 and 29.8 kg/m 2 but also in the middle of the distribution of waist circumference. Price et al (2006) studied 14 833 subjects aged 75 years or older (follow-up 5.9 years, 649 deaths). In non-smoking men and women (90% of the cohort), compared with the lowest quintile, the hazard ratios were below 1.0 for all other quintiles of BMI.…”
mentioning
confidence: 99%